The application of the Bill of Rights - Borman, P J (Department of Public Law, 2021)
For centuries South Africa has been embroiled in racial conflict with human rights as one of the tragic casualties. With the adoption of the lnterim and Final Constitutions a decisive break was made with the past. One of the foundations laid to forge our new society based on equality and human dignity was the adoption of a Bill of Rights. Embodied in the clauses of the Bill of Rights are the values by which the people should guide their conduct in the future.